2017
DOI: 10.1016/j.crad.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of imaging abnormalities of the subcallosal septal area with Alzheimer's disease and mild cognitive impairment

Abstract: AimTo evaluate the use the distance between the adjacent septal nuclei as a surrogate marker of septal area atrophy seen in Alzheimer's disease (AD).Materials & MethodsInterseptal distance (ISD) was measured, blind to clinical details, in 250 patients who underwent computed tomography (CT) of the brain at University Hospital of Wales. Clinical details including memory problem history were retrieved. An ISD cut-off value that discriminated those with and without memory symptoms was sought. ISD measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Weight loss commonly occurs in prodromal and clinical stages of AD ( White et al, 1996 ; Sergi et al, 2013 ), and mouse models of AD exhibit hypothalamic gene expression levels that correlate to both weight loss and cognitive deficits ( Dai et al, 2022 ). The septum and pallidum have been reported to undergo AD-related morphological changes ( Teipel et al, 2005 ; Gan et al, 2017 ), elicit hippocampal theta oscillations ( Hangya et al, 2009 ; Chee et al, 2015 ), and modulate hippocampal epileptogenesis ( Miller et al, 1994 ), which is observed in human AD patients ( Lam et al, 2017 ) and AD mouse models ( Palop and Mucke, 2009 ). Lastly, the habenula is implicated in motivation and behavioral regulation ( Hikosaka et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss commonly occurs in prodromal and clinical stages of AD ( White et al, 1996 ; Sergi et al, 2013 ), and mouse models of AD exhibit hypothalamic gene expression levels that correlate to both weight loss and cognitive deficits ( Dai et al, 2022 ). The septum and pallidum have been reported to undergo AD-related morphological changes ( Teipel et al, 2005 ; Gan et al, 2017 ), elicit hippocampal theta oscillations ( Hangya et al, 2009 ; Chee et al, 2015 ), and modulate hippocampal epileptogenesis ( Miller et al, 1994 ), which is observed in human AD patients ( Lam et al, 2017 ) and AD mouse models ( Palop and Mucke, 2009 ). Lastly, the habenula is implicated in motivation and behavioral regulation ( Hikosaka et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inter-septal distance (ISD) is defined as the minimum distance between the septal nuclei of each hemisphere. In accordance with the methodology outlined by Gan and colleagues, [11] the distance between the medial convexities of the septal nuclei of each hemisphere, posterior to the anterior cerebral arteries, was used for this marker. This measurement was performed on T1 images by an expert neurologist (PAB).…”
Section: Methodsmentioning
confidence: 99%
“…Larger MTA scores have been associated with global cognitive impairment one year after ischaemic stroke [10] . Additionally, the interseptal distance (ISD), or distance between adjacent septal nuclei, has recently been proposed as a practical measure of septal atrophy seen in AD, and has shown high sensitivity and specificity for distinguishing patients with and without memory impairment as well as MCI patients from controls [11] and so may be a valid marker of neurodegeneration. The clinical utility of these low-cost measures have not been thoroughly explored in the cont of predicting cognitive impairment in a TIA population.…”
Section: Introductionmentioning
confidence: 99%
“…Milder ISD increase can be seen in mild cognitive impairment (MCI). 1 Paradoxical septal area hypertrophy (antiepileptic septal-hippocampal system) may be seen in MTS due to seizure related increased retrograde transport of nerve growth factor from hippocampus to septal area. 2
Figure 1.Sagittal graphic (a) and consecutive parasagittal to midline sagittal 3D FLAIR images (b–d) demonstrating the 3-arches configuration of limbic system.
…”
Section: Limbic Systemmentioning
confidence: 99%
“…Milder ISD increase can be seen in mild cognitive impairment (MCI). 1 Paradoxical septal area hypertrophy (antiepileptic septalhippocampal system) may be seen in MTS due to seizure related increased retrograde transport of nerve growth factor from hippocampus to septal area. 2 Hippocampus (Figure 2) consists of two distinctive layers of GM, namely, cornu ammonis (CA) and gyrus dentatus (GD).…”
Section: Limbic Systemmentioning
confidence: 99%